New insights into guidance laws with terminal angle constraints - Lee, Chang-Hun; Seo, Min-Guk (AIAA, 2018)
Introduction : In the field of guidance technology, advanced guidance laws are being developed using various control theories such as optimal control [1,2], sliding mode control [3–6], H-infinity control [7], the state-dependent Riccati equation [8], the Lyapunov theory [9], the geometric control theory [10], predictive control [11,12], and feedback linearization control [13]. The general procedure of this approach is to first establish the guidance problem to be solved and to define the guidance geometry and kinematics equation corresponding to the guidance problem. A guidance law is then systematically designed in such a way that an appropriate control theory is applied to a predetermined guidance problem. The potential importance of this approach is that a number of advanced guidance laws can be newly developed, depending on the combinations of guidance problems and control theories. Therefore, recent trends in the design of guidance laws focus on finding a new combination of guidance problems and control theory to obtain a new guidance law that is superior to the conventional guidance law. Although previous research has focused more on the methodology and the design process itself, little effort has been made toward understanding the characteristics of the newly developed guidance laws.